Amplified Victimization: Contextualizing Misogynoir, Sex Trafficking, and Trauma - Gonzalez, Cassandra Mary Frances (Victims & offenders, 2025)
Research has historically defined sex trafficking victimization as a “gendered” problem because most identified victims are women and girls. While the gendered nature of exploitation cannot be ignored, this approach erases specific vulnerabilities in trafficking predation. Extant research shows that Black women and girls are often criminalized in anti-trafficking efforts and not considered “real” victims. This is because while Black women and girls suffer gendered violence, they do not have the privilege of being perceived as just “women” or “girls”—they are Black women and girls. Drawing on in-depth interviews with 28 Black women survivors, this article explores their experiences disclosing their victimization to criminal justice agents. Grounded in intersectional criminology and Black feminism, this article introduces the concept Amplified Victimization, which is the multiplicative effect of trauma and victimization that is intensified or compounded by criminalization, further abuse, or apathy from criminal legal agents and the institution. The article provides a victimization framework that can be applied to all disenfranchised groups experiencing harm and violence and have historically been marginalized as victims by the criminal legal system.